2018
DOI: 10.1101/474312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Class of Inferior Colliculus Principal Neurons Labeled in Vasoactive Intestinal Peptide-Cre Mice

Abstract: 10Located in the midbrain, the inferior colliculus (IC) is the hub of the central auditory system. Although 11 the IC plays important roles in speech processing, sound localization, and other auditory computations, 12 the organization of the IC microcircuitry remains largely unknown. Using a multifaceted approach in 13 mice, we have identified vasoactive intestinal peptide (VIP) neurons as a novel class of IC principal 14 neurons. VIP neurons are glutamatergic stellate cells with sustained firing patterns. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 97 publications
3
21
0
Order By: Relevance
“…Those experiments were conducted in young animals and could potentially reflect mechanisms that disappear after the system has developed (see Morley and Happe, 2000 for a discussion of separate cholinergic roles during and after the development of the auditory system). In a preliminary study, Rivera-Perez et al ( 2020 ) demonstrated direct nicotinic depolarization of VIP-expressing IC cells (which are known to be glutamatergic; Goyer et al, 2019 ). Additional experiments will be needed to identify the receptor types on glutamatergic and GABAergic IC cells and to differentiate presynaptic vs. postsynaptic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Those experiments were conducted in young animals and could potentially reflect mechanisms that disappear after the system has developed (see Morley and Happe, 2000 for a discussion of separate cholinergic roles during and after the development of the auditory system). In a preliminary study, Rivera-Perez et al ( 2020 ) demonstrated direct nicotinic depolarization of VIP-expressing IC cells (which are known to be glutamatergic; Goyer et al, 2019 ). Additional experiments will be needed to identify the receptor types on glutamatergic and GABAergic IC cells and to differentiate presynaptic vs. postsynaptic effects.…”
Section: Discussionmentioning
confidence: 99%
“…This gap in knowledge has eluded the field mostly due to the complexity of the neuronal populations in the IC, where it has proven difficult to identify and study specific neuron classes using conventional approaches. We recently overcame this obstacle, identifying vasoactive intestinal peptide (VIP) neurons as the first molecularly identifiable neuron class in the IC (Goyer et al, 2019). Vasoactive intestinal peptide neurons are found throughout the major IC subdivisions, they are glutamatergic, and they have a stellate morphology with spiny dendrites that, within the central nucleus of the IC (ICc), typically extend across two or more isofrequency laminae.…”
Section: Introductionmentioning
confidence: 99%
“…Num. MAB5406, RRID: AB_2278725; Anstotz, Karsak, & Rune, ; Chuhma, Mingote, Moore, & Rayport, ; Goyer et al, ; Orefice et al, ; Tulloch, Teo, Carvajal, Tessier‐Lavigne, & Jaworski, ). GAD67 is an enzyme that catalyzes the synthesis of GABA and encoded by Gad1 gene (Pinal & Tobin, ).…”
Section: Resultsmentioning
confidence: 99%